The Idea of Implementation Of Cloud Computing Technology In MSME Booking System - Sherley, Sherley; Herdina, Herdina; Veren, Veren (Journal of Information System and Technology (JOINT), 2024)
MSMEs (Micro and Small and Medium Enterprises) have an important role now in the economy. 96% of companies in ASEAN are MSMEs. Although MSMEs have shown their role, they still face various obstacles and constraints such as lack of information, transaction record tech, weak branding, promotion and infrastructure. The application of information technology will certainly make it easier for MSMEs to strengthen branding, business processing and enable cooperation with other parties to provide added value to MSMEs. The application of cloud computing or cloud computing is considered suitable for MSMEs that have limited resources in the form of capital, human resources (HR) and information technology infrastructure. Responding to the importance of the application of information technology to these MSMEs, the research aims to design and build systems that can facilitate MSMEs by utilizing cloud computing technology with SAAS (software as a service). The system expectedly can produce the output which are the record of the transaction and its report for supporting the MSMEs business.